Escovopsioides nivea is a non-specific antagonistic symbiont of ant-fungal crops. (April 2022) - Pietrobon, Tatiane de Castro; Kooij, Pepijn Wilhelmus; Montoya, Quimi Vidaurre; Rodrigues, Andre
Abstract: Fungus-growing attine ants maintain a mutualistic relationship with basidiomycete fungi which they cultivate for food. In addition to the fungal partner, attine ant colonies harbor a myriad of microorganisms, including the genus Escovopsis, fungal parasites of the ant crops. Because Escovopsioides nivea is phylogenetically close to Escovopsis, previous studies assumed it has a negative interaction in the ant-fungus association. Here, we present an extended phylogeny of E. nivea based on new collections from different attine ant genera found in different localities. We also carried out co-culture experiments between E. nivea with different fungal cultivars. Our results suggest E. nivea is a symbiont of attine ant colonies, which inhibits the growth of fungal crops, supporting the hypothesis it is antagonistic to the system. However, the patterns of interaction between E. nivea and fungal crops differ from those shown by Escovopsis, suggesting a different evolution from that of the parasite. Highlights: Escovopsioides nivea has been repeatedly found in attine ant colonies. E. nivea inhibited diverse ant fungal cultivars but did not show preference for any of them. E. nivea growth was inhibited by Apterostigma cultivars. E. nivea is yet another antagonistic fungal symbiont found in the attine ant colonies.